Adsorption of chain molecules in pores with crystalline walls: a density functional approach - Bucior, K.; Patrykiejew, A.; Sokołowski, S.; Pizio, O. (Condensed Matter Physics, 2009)
A microscopic density functional theory of adsorption of chain molecules on the attractive solid surfaces of crystalline symmetry is developed. The proposed approach is based on the expansions of one-particle functions into two-dimensional Fourier series. Illustrative calculations for dimers, 8- and 16-mers adsorbed on a (100) fcc crystal surface indicate the effect of the periodicity of the adsorbing potential on the structure of the adsorbed layer and thermodynamics of adsorption.